Sosialisasi dan Pelatihan Pembuatan Pupuk Organik Cair (POC) dari Sampah Rumah Tangga bagi Ibu PKK Kelurahan Rantau Panjang Kecamatan Rumbai Barat Kota Pekanbaru - Mayta Novaliza Isda; Elsya Desviyanti; Elli Indriana Putri; Najmi Fadhila Nithami; Muhammad Tamyis Lutfi Hakim; Dhini Yulianti; Riski Saputra; Rizal Noor; Mimi Safitri; Maulana Ishak; Ismu Sodaqti (Yayasan Kajian Riset Dan Pengembangan Radisi, 2022)
Garbage is a big problem that is difficult to solve, especially in Indonesia. Therefore, efforts are needed to reduce waste. Based on data from the Ministry of Environment and Forestry, in 2020 the total national waste stockpile in Indonesia will reach 67.8 tons. One type of organic waste comes from household waste such as vegetables, fruits, fish, meat, and so on. In Rantau Panjang Village, household waste can still be found which is very disturbing to the community. So, of this problem, the Balek Village Community Service Team, Rantau Panjang Village, and Riau University created a program to utilize the waste to be used as Liquid Organic Fertilizer (POC). The purpose of this activity is to overcome the waste problem in Rantau Panjang Village and provide skills training to PKK women in Rantau Panjang Village in utilizing household waste to produce Liquid Organic fertilizers (POC). The method in this service activity is social engineering in the form of socialization and direct training. Through this activity, it is hoped that PKK mothers can easily understand the material presented so that they can make innovations in utilizing household waste.